2019
DOI: 10.1111/aor.13467
|View full text |Cite
|
Sign up to set email alerts
|

Interference in the anti‐Xa heparin activity assay due to hemolysis and icterus during pediatric extracorporeal life support

Abstract: Chromogenic anti‐Xa assays for unfractionated heparin monitoring (heparin activity) are susceptible to interference from hemolysis and icterus. The purpose of this study was to better understand the effect of hemolysis and icterus on anti‐Xa heparin activity and to predict the magnitude of the error. Increasing levels of hemoglobin and unconjugated bilirubin were added to pooled normal plasma or buffer containing known levels of heparin. Increased plasma hemoglobin or bilirubin produced falsely increased resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In addition, analytical interferences on anti-Xa activity, including antithrombin deficiency (for the kits that do not add exogenous antithrombin to the reagents), hemolysis or hyperbilirubinemia due to the photo-optical detection method used, may also occur [ 9 , 28 ]. According to two previous studies, increased plasma-free hemoglobin concentrations resulted in a concentration-dependent underestimation of heparin activity [ 29 , 30 ]. As a consequence of shear stress and the exposure of blood to non-biological substances in ECMO patients, thrombocytopenia and altered platelet function may occur due to decreased levels of adhesion receptors, activation markers and surface expression of CD62/CD63 [ 9 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, analytical interferences on anti-Xa activity, including antithrombin deficiency (for the kits that do not add exogenous antithrombin to the reagents), hemolysis or hyperbilirubinemia due to the photo-optical detection method used, may also occur [ 9 , 28 ]. According to two previous studies, increased plasma-free hemoglobin concentrations resulted in a concentration-dependent underestimation of heparin activity [ 29 , 30 ]. As a consequence of shear stress and the exposure of blood to non-biological substances in ECMO patients, thrombocytopenia and altered platelet function may occur due to decreased levels of adhesion receptors, activation markers and surface expression of CD62/CD63 [ 9 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may also experience high levels of fibrinogen during their ECMO course, to which anti-Xa assays are not sensitive. All of these conditions frequently encountered in patients on extracorporeal devices may therefore lead to inadequate UFH dosing [ 29 , 30 , 31 , 32 ]. Since 48.6% of the patients included in this study were on ECMO (8.6%) or CVVH (40.0%), this led to a poorer correlation between POCT-APTT and anti-Xa pairs.…”
Section: Discussionmentioning
confidence: 99%
“…50 mg/dL) had significantly lower anti-FXa activity despite an identical UFH infusion rate, with a median difference approaching 0.1 IU/mL. Khan and Chandler, in a very recent study, 25 found that samples with large free hemoglobin concentration (228 mg/dL) showed an underestimation of the UFH concentration by 0.21 IU/mL; interference between free hemoglobin, bilirubin, and anti-FXa activity was noticed for free hemoglobin values greater than 70 mg/dL or bilirubin greater than 16 mg/dL, conditions that were found in 16 and 26% of pediatric patients under extracorporeal life support. In both these studies, the anti-FXa activity was measured using the Stago liquid anti-FXa assay (Diagnostica Stago).…”
Section: Chromogenic Pollutionmentioning
confidence: 94%
“…Jenna Khan and Wayne L. Chandler of the University of Washington, Seattle, WA, USA investigated the interferences in the anti‐Xa heparin activity assay due to hemolysis and icterus during pediatric ECLS. Increasing levels of hemoglobin and unconjugated bilirubin were added to pooled normal plasma or buffer containing known levels of heparin.…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%